2012
DOI: 10.1007/s10552-012-9986-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Pacific people in New Zealand

Abstract: Pacific people in New Zealand have a disproportionate cancer burden related to infectious diseases such as HPV and Hepatitis B. However, with escalating evidence for causal associations between diabetes, obesity, and physical inactivity with various cancers, the challenge will be to prevent these cancers from rising in Pacific people who have the highest rates of these conditions in New Zealand. Disparities for tobacco-related cancers support tobacco consumption as another important cause of cancer incidence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 69 publications
(62 reference statements)
5
22
0
Order By: Relevance
“…Similar hypotheses can be proposed in regard to the higher risk of OPC in NZ Māori, but these hypotheses are speculative and more detailed studies are needed. Pacific Peoples in NZ have higher rates of several cancers related to HPV and Hepatitis B, and have the highest rates of obesity and diabetes in NZ 33 . The role of these factors in OPC and OCC has been little studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similar hypotheses can be proposed in regard to the higher risk of OPC in NZ Māori, but these hypotheses are speculative and more detailed studies are needed. Pacific Peoples in NZ have higher rates of several cancers related to HPV and Hepatitis B, and have the highest rates of obesity and diabetes in NZ 33 . The role of these factors in OPC and OCC has been little studied.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the rate of HCC in the Pacific is 7 and 4 times higher than that in Europe for males and females, respectively [111]. …”
Section: Epidemiology Of Hcc In Asia–pacific Countriesmentioning
confidence: 99%
“…Other authors have suggested race, ethnicity, and nativity as contributing factors . In Sweden, immigrants from the middle east, Asia, and South America have an increased incidence of well‐differentiated thyroid cancer, and in New Zealand, women from Pacific regions have a higher incidence in comparison with women of European descent . However, other authors did not find differences associated with race in the US population .…”
Section: Introductionmentioning
confidence: 95%